Systematic Literature Review On The Influence Of Organizational And Personal Factors On Quiet Quitting With Employee Well Being As A Mediating Variable - Asyip Abdul Mu’iz Annasihi; Muhammad Irfan Syaebani (DAS Institute, 2026)
This study aims to analyze the influence of organizational and personal factors on quiet quitting behavior with employee well-being as a mediating variable through a Systematic Literature Review approach. The study was conducted to understand the growing phenomenon of employee disengagement in modern workplaces and identify the factors contributing to reduced work involvement. The review process used the PRISMA method by collecting articles from several academic databases, including Google Scholar, Scopus, ScienceDirect, Emerald Insight, and SpringerLink. A total of 226 articles were initially identified, and after the screening and eligibility process, 10 main journal articles published between 2022–2026 were selected for analysis, supported by 17 additional references. The findings indicate that organizational factors such as perceived organizational support, workload, leadership, organizational culture, and quiet firing significantly influence employee well-being and quiet quitting behavior. Personal factors including psychological capital, motivation, emotional intelligence, and resilience also affect employees’ ability to manage stress and maintain work engagement. The study further reveals that employee well-being plays an important mediating role between organizational and personal factors and quiet quitting behavior. Employees with positive well-being tend to demonstrate stronger commitment, higher engagement, and better emotional attachment to their work. The study highlights the importance of supportive organizational practices and psychological resources in reducing quiet quitting behavior and improving employee well-being in the workplace.